2015
DOI: 10.1177/1087054715594422
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Study Skills and Parent Education on First-Year GPA Among College Students With and Without ADHD: A Moderated Mediation Model

Abstract: Objective To test if the relationship between ADHD and academic achievement is mediated by service utilization and/or study skills, and if these mediation effects are moderated by parental education level. Method A bootstrapping method within structural equation modeling was used with data from 355 first year college students meeting strict criteria for ADHD or clearly without ADHD to test the mediation and moderation effects. Results Study skills, but not service utilization, significantly mediated the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 47 publications
4
26
0
1
Order By: Relevance
“…Furthermore, inattention, difficulties sustaining attention and vigilance may further impair college students’ abilities to attend to important information and manage their coursework and personal life during the college years. A study conducted by our research team (Gormley et al, 2015), using the current dataset, corroborated this pattern; students with ADHD had lower GPAs and self-reported poorer study skills than students without ADHD. Overall, these findings underscore the need for developing interventions to assist college students in developing strategies to cope with these areas of difficulty (Anastopoulos & King, 2015; Fuermaier et al, 2015; Isquith et al, 2006; Martinussen, Hayden, Hogg-Johnson, & Tannock, 2005; Van Ewijk et al, 2014; Weyandt, 2009; Weyandt et al, 2014).…”
Section: Discussionsupporting
confidence: 75%
“…Furthermore, inattention, difficulties sustaining attention and vigilance may further impair college students’ abilities to attend to important information and manage their coursework and personal life during the college years. A study conducted by our research team (Gormley et al, 2015), using the current dataset, corroborated this pattern; students with ADHD had lower GPAs and self-reported poorer study skills than students without ADHD. Overall, these findings underscore the need for developing interventions to assist college students in developing strategies to cope with these areas of difficulty (Anastopoulos & King, 2015; Fuermaier et al, 2015; Isquith et al, 2006; Martinussen, Hayden, Hogg-Johnson, & Tannock, 2005; Van Ewijk et al, 2014; Weyandt, 2009; Weyandt et al, 2014).…”
Section: Discussionsupporting
confidence: 75%
“…Previous work with the TRAC sample indicated significant differences between students with and without ADHD on cumulative first-year GPA (Gormley et al, 2015); however, the present study analyzed GPA at three time points separately. Interestingly, the data suggest a trend such that the effect size of group differences on GPA decreases over time, with the largest differences being evident in high school and the smallest effect sizes existing by the second semester of the first year at college.…”
Section: Discussionmentioning
confidence: 74%
“…Moreover, college students with ADHD have shown significant deficits in these study skills as compared to their peers (Gormley et al, 2015; Norwalk, Norvilitis, & MacLean, 2009; Reaser et al, 2007). In fact, a recent study found study skills to mediate the association between ADHD and GPA (Gormley et al, 2015). However, SCT and ADHD symptoms commonly co-occur (Becker & Barkley, in press; Becker, Leopold et al,2016), and there is emerging evidence that supports the hypothesis that SCT is uniquely related to study skills.…”
Section: Sct and Academic Functioningmentioning
confidence: 99%